2022
DOI: 10.3892/or.2022.8446
|View full text |Cite
|
Sign up to set email alerts
|

DPP3 expression promotes cell proliferation and migration in vitro and tumour growth in vivo, which is associated with poor prognosis of oesophageal carcinoma

Abstract: Dipeptidyl peptidase III (DPP3), a zinc-dependent metallopeptidase, is upregulated in a variety of malignancies. However, little is known about its roles in the pathogenesis of these malignancies. The present study was designed to investigate the roles of DPP3 in the pathogenesis and progression of oesophageal cancer (EC). The expression level of DPP3 in EC tissues and adjacent normal tissues was detected in 93 cases of tissue biopsies collected from patients diagnosed with oesophageal carcinoma by immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Likewise, DPP3 down-regulation led to a higher apoptotic rate in these cells. This agrees with a recent report demonstrating that DPP3 down-regulation is associated with an enhancement in the expression of proapoptotic proteins and alteration in cell cycle distribution in ESCC cells [ 32 ]. The reduced proliferation rate and higher apoptotic rate in DPP3 knockdown cells might also be responsible for the observed reduction in colony size of ESCC cells after DPP3 knockdown.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Likewise, DPP3 down-regulation led to a higher apoptotic rate in these cells. This agrees with a recent report demonstrating that DPP3 down-regulation is associated with an enhancement in the expression of proapoptotic proteins and alteration in cell cycle distribution in ESCC cells [ 32 ]. The reduced proliferation rate and higher apoptotic rate in DPP3 knockdown cells might also be responsible for the observed reduction in colony size of ESCC cells after DPP3 knockdown.…”
Section: Discussionsupporting
confidence: 93%
“…DPP family members have emerged as critical regulators of cellular physiology [ 19 ]. Several reports on DPP3 have suggested its aberrant activity in cancers of multiple origins, such as breast cancer [ 20 , 26 , 42 ], lung cancer [ 24 ], ovarian cancer [ 22 ], endometrial cancer [ 22 ], colon cancer [ 30 ], and EC [ 32 ]. Many of these studies observed higher expression or activity of this peptidase in tumor tissues compared with normal tissues, suggesting its overexpression is common in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the current knowledge of DPP3 and SH2D3C and our own findings, we propose that their interaction represents a link between NRF2–KEAP1 mediated oxidative stress response and the regulation of cell migration through the NSP–Cas network. Currently, there is no evidence that these signaling pathways are related; however, there are reports that DPP3 depletion by shRNA reduces the cell migration of colon cancer cell lines HCT-116 and RKO [ 18 ] and esophageal cancer cell lines Eca-109 and TE-1 [ 28 ], although the exact mechanism of DPP3 involvement in cell migration was not elucidated. In addition, both DPP3 and p130Cas (interactor of SH2D3C) have been linked to bone development through the regulation of osteoclasts.…”
Section: Discussionmentioning
confidence: 99%
“…A human apoptosis antibody array (Abcam, USA, Cat. Ab134001) was used to detect the expression levels of 43 human apoptosis markers [24][25][26]. T24 cells transfected with lentivirus were washed with PBS and lysed using cell lysis buffer.…”
Section: Cell Apoptosis Assaymentioning
confidence: 99%